Red memory : the afterlives of China's Cultural Revolution - Branigan, Tania (W.W. Norton & Company, 2023)
"'It is impossible to understand China today without understanding the Cultural Revolution,' Tania Branigan writes. During this decade of Maoist fanaticism between 1966 and 1976, children turned on parents, students condemned teachers, and as many as two million people died for their supposed political sins, while tens of millions were hounded, ostracized, and imprisoned. Yet in China this brutal and turbulent period exists, for the most part, as an absence; official suppression and personal trauma have conspired in national amnesia. Red Memory uncovers forty years of silence through the stories of individuals who lived through the madness"--